Peran Broadcasters dan Brand Image dalam Meningkatkan Loyalitas Konsumen — Bukti dari Live Streaming di Platform E- commerce Shopee - Gugyh Susandy; Rizal Septiana (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2025)
This study aims to analyze the role of Broadcasters and Brand Image in enhancing consumer loyalty on the Shopee e-commerce platform, particularly through the live streaming feature. This research employs a quantitative method with a descriptive approach, involving 100 respondents who are users of Shopee Live in Subang Regency and customers of the "Tokokarungjantan" store. Data were collected through questionnaires and analyzed using validity, reliability, normality, multicollinearity, heteroscedasticity tests, and multiple linear regression analysis. The results show that Brand Image has a positive and significant influence on consumer loyalty, while Broadcaster has no significant effect. The regression analysis indicates that a strong brand image can enhance consumer loyalty, whereas the role of broadcasters in live streaming, although important for influencing consumer engagement, does not significantly contribute to loyalty. The implications of this research emphasize the importance of strengthening brand image in digital marketing strategies, particularly in the e-commerce context. Additionally, this study recommends improving the quality of Broadcasters in live streaming to boost consumer engagement and loyalty. Future research is expected to identify other variables affecting consumer loyalty and expand the scope of the study to different market segments.